STATUS FUNGSIONAL SEBAGAI FAKTOR DETERMINAN KUALITAS HIDUP LANSIA PASCA STROKE DI JAKARTA SELATAN - Lestari, Puspita Hanggit (Jurnal Kesehatan Holistic, 2017)
Functional changes in elderly post-stroke can affect the elderly and families physically, psychologically, socially, and spiritually. Focusing on the impact of stroke for the elderly and families, then the purpose of this study was to identify functional status as determinant factor of elderly’s post-stroke quality of Life. This cross-sectional study using purposive sampling with 70 respondents post-stroke elderly who live with their families in South Jakarta. The study evaluated the burden of caregivers with Zarit Burden Interview, the elderly's quality of life after a stroke with SS-QOL 12, social support with MOS-SSS and functional status with IADL. A linear regression model used in the study to identify determinant factors of quality of life. The results showed that functional status is dominant factor of quality of life. Conclusion of the study is the high functional status associated with high quality of life of the elderly post-stroke. Community Nurses and family have an important in rehabititation of elderly’s stroke. . Key words : elderly post-stroke, caregiver, quality of life, caregiver burden